Development and validation of a postoperative risk model for esophageal squamous cell carcinoma after neoadjuvant immunochemotherapy - Zhang, Hai; Li, Cui; Lin, Jiangbo; Xie, Xihao; Peng, Fengyuan; Feng, Caihou; Che, Weibi; Huang, Jiawei; Wu, Bomeng (Frontiers in Medicine, 2025)
BackgroundEsophageal squamous cell carcinoma (ESCC) remains a highly aggressive malignancy with a significant risk of recurrence, even after curative treatment. While neoadjuvant immunochemotherapy (nICT) combined with minimally invasive esophagectomy (MIE) has shown promise in improving outcomes for patients with locally advanced, resectable ESCC, the factors contributing to early postoperative recurrence remain unclear. This study aims to identify high-risk factors for short-term recurrence and develop a predictive model for recurrence in patients with locally advanced, resectable ESCC treated with nICT followed by MIE (McKeown approach).MethodsPatients with locally advanced, resectable ESCC who underwent nICT followed by MIE at Gaozhou People’s Hospital between 1 January 2019, and 1 January 2022, were consecutively included in the training set. Patients who received the same treatment at Union Hospital of Fujian Medical University during the same period were included as the validation set. A recurrence prediction model was developed based on these cohorts.ResultsA total of 362 patients treated with nICT were included, including 218 in the training set and 144 in the validation set. Least absolute shrinkage and selection operator regression identified the 10 most significant variables associated with recurrence: smoking history, drinking history, diarrhea, number of lymph nodes dissected, number of lymph node dissection stations, pathological N (pN) stage, pathological TNM stage, tumor regression grade, nerve invasion, and postoperative arrhythmia. Multivariate regression analysis further identified pN+ and nerve invasion as independent high-risk factors for recurrence. The recurrence prediction model demonstrated strong discriminatory ability, with an area under the curve of 0.92 in the training set and 0.91 in the validation set at 3 years postoperatively. Survival analysis showed a statistically significant difference (p < 0.05) in the 3-year overall survival and recurrence-free survival between risk groups. In the low-risk group, postoperative adjuvant therapy did not provide a survival benefit; in the high-risk group, it significantly improved outcomes.ConclusionPatients with locally advanced ESCC treated with nICT followed by MIE who have a high pN stage and pathological evidence of nerve invasion may benefit from intensified adjuvant therapy to improve long-term survival.